The Legal Protection for the Recognition of Customary Right in Agrarian Regulations - Indriasari, Evy; Widyastuti, Tiyas Vika (International Journal of Law Reconstruction, 2024)
The purpose of this research, to find out the extent to which customary law community land rights are recognized in Indonesian legislation. This article is legal research type of library research by using a statutory regulatory approach (Statute Approach). For customary law communities, Land is part of their lives that is controlled and managed jointly with the responsibility given by nature to maintain and protect it. In reality, a lot of customary land has been taken by the government and used as agricultural land, Even though customary law communities have legal standing regulated in the 1945 Constitution, Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles, MPR Decree No. IX/2001, Law Number 39 of 1999 concerning human rights. However, in reality, the government still takes customary land which is then given to investors to manage. This of course infringes the rights of customary law communities. This problem is exacerbated because in article 5 paragraph (1) of Law number 41 of 1999 concerning Forestry states that customary forests are part of state forests.